Comparison Of Patients Emergency With Pre And Post Covid-19 Digestive Surgery - Sayuti, Muhammad; Iqbal, Teuku Yudhi; Salsabila, Salsabila (Fakultas Kedokteran Universitas Malikussaleh, 2023)
An emergency situation is a situation that must require treatment or action as soon as possible to avoid threatening the patient's life. At the end of 2019, there was an outbreak of a virus called COVID-19 which originated in China. This virus outbreak spread very quickly, in a matter of months it had spread to all countries including Indonesia. During the COVID-19 period, doctors had to choose which surgery was an emergency and which disease could still be cured with drugs. Surgeons also had to comply with the protocols made by the Indonesian Surgeon Association (PABI). This type of research is descriptive type, with a total sample of 136.The results of this study showed a decrease in the number of visits for digestive surgery patients by 4.41%. In 2019 there were 71 patients and in 2020 there were 65 patients. With the following characteristics: in 2019 the majority of digestive surgery patients are over 65 years old (22.5%), in 2020 the majority of digestive surgery patients are 36-45 years old (15.4%). Gender in 2019 is mostly male (53.5%) female (46,5%) and the majority in 2020 is male (66.2%) female (33,8%). The most common diagnosis in 2019 was HIL incarceration (23.9%) and in 2020 the most diagnosed was peritonitis ec perforation app (21.5%). The most surgical procedure in 2019 was hernioraphy (26.8%) and in 2020 the most surgical procedure was laparotomy appendectomy (21.5%). From the results of this study it can be concluded that the number of visits during the pandemic decreased by 4.41%.